Constructing sex offending against children: A content analysis of the Globe & Mail, 1970--2005 - Grondin, Anne-Marie (University of Ottawa (Canada), 2006)
Discursive practices on sex offending against children are value-laden, often eliciting strong social reactions due to the sensitive nature of the topic and anxieties which are born of the rhetoric of several claims-makers. Despite research findings which could help reduce the level of anxiety, stereotypes and common assumptions prevail. Furthermore, the media tends to represent sex offending in a simplified and distorted manner. Lurid and partial portrayals of child sex offending are highly problematic both for immediate victims, and for society as a whole, considered here to be a collateral victim of a level of social reaction so radicalized it can be characterized as pedophobic. In order to explore whether media portrayals change over time, I examined portrayals of child sex offending in the Globe & Mail between 1970 and 2005. In so doing, I accounted for the social context in which these media portrayals were constructed. Quantitatively, the number of articles increased exponentially between 1970 and 2005. These portrayals also changed over time with respect to their content. These findings point to a third conclusion---that child sex offending is socially constructed through the media. Through processes of simplification, and by ignoring the totality of the problem, the media misrepresent child sex offending.
Keywords: Journalism.; Sociology, Criminology and Penology.